Evaluation of Female Cases Applying to Mersin Medical Faculty Hospital Due to Partner Violence Between 2018-2020 - Işık, Hammet; Gamsız Bilgin, Nursel (The Bulletin of Legal Medicine, 2023)
Objective: It is aimed to medicolegal evaluation of risk factors and to discuss in the light of literature, depending on sociodemographic data, causes of violence and physical/mental pathologies in women who were sent to the Forensic Medicine outpatient clinic with the claim of being subjected to partner violence. Methods: The data of female cases sent between 01.01.2018 and 31.12.2020 were retrospectively scanned in terms of sociodemographic data, degree of physical violence and mental illnesses related to violence. It was evaluated using the SPSS package program. Results: The mean age of 143 female cases was 35.8±10.7, women with low educational and economic level and unemployed were exposed to more physical violence by their partners, 88.1% were exposed to physical violence, 54.5% were injured in the facial region. Bone fractures were detected in 16.4%, and severe mental illness developed in 45.9%. In addition, it was determined that the risk of suicide attempt was high in cases who were exposed to violence for many years and were diagnosed with a violence-related mental illness. Conclusion: It has been observed that low education and economic level, unemployment constitute a higher risk group for women to be subjected to physical violence by their partners. We believe that, together with the urgent legal regulations to prevent violence, the development of projects to increase the education level of women, create jobs and gain economic freedom will provide significant contributions and benefits to the prevention of violence.